Clinico-bacteriological profile and antibiotic resistance pattern in patients with acute exacerbation of COPD - Narayan Mood; Surendar Reddy Katta; Aruna Kumari Badam; Jayaram Chundru (SpringerOpen, 2022)
Abstract Background Repeated attacks of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have been attributed to bacterial infections. However, sputum microbiology for identifying the bacteriological profile is not performed usually and remains controversial. Thus, we performed a prospective, cross-sectional study to assess the clinico-bacteriological profile of the patients with AECOPD and antibiotic resistance pattern of bacteria isolated from sputum samples. The study involved 104 consecutive hospitalized patients, of either gender, aged 40-90 years, and diagnosed with AECOPD. Before initiating an empirical antibiotic therapy, the sputum samples of all the patients were collected and subjected to Gram staining, bacterial culture, and antibiotic sensitivity. Results The most common bacterial isolates were P. aeruginosa (30.7%) followed by K. pneumoniae (20.3%) and S. pneumoniae (8.6%). Both Gram-positive and Gram-negative bacteria were most sensitive to Meropenem (91%) followed by Amoxicillin-clavulanic acid (83%). However, these bacteria were most resistant to Cefoperazone-sulbactam (43%) followed by Levofloxacin (41%). P. aeruginosa and K. pneumoniae were most resistant to Cefoperazone-sulbactam (23%) followed by Fluoroquinolones (23-35%), while S. pneumoniae was most resistant to Ciprofloxacin (44%) followed by Amoxicillin-clavulanic acid (33%). Conclusions Isolation of P. aeruginosa, as the most common agent, further confirms its roles in severe attacks of AECOPD. The regularly used antibiotics were found to be resistant to most isolates, thereby suggesting that severity of AECOPD may be attributed to the prevalence of antibiotic-resistant strains.